2022
DOI: 10.3390/nano12030425
|View full text |Cite
|
Sign up to set email alerts
|

Optical Mode Tuning of Monolayer Tungsten Diselenide (WSe2) by Integrating with One-Dimensional Photonic Crystal through Exciton–Photon Coupling

Abstract: Two-dimensional materials, such as transition metal dichalogenides (TMDs), are emerging materials for optoelectronic applications due to their exceptional light–matter interaction characteristics. At room temperature, the coupling of excitons in monolayer TMDs with light opens up promising possibilities for realistic electronics. Controlling light–matter interactions could open up new possibilities for a variety of applications, and it could become a primary focus for mainstream nanophotonics. In this paper, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…In this Special Issue “2D Nanostructures for Optoelectronic and Green Energy Devices”, we have collected nine high-quality, original research papers and one comprehensive review paper by outstanding scientists and engineers from relevant fields, covering the topics in optical properties and couplings in 2D nanostructures, [ 5 , 6 , 7 , 8 ] spectroscopic analysis in atomic scale, [ 9 ] 2D transistors, [ 10 , 11 ] 2D optoelectronics, [ 12 ] and 2D energy storage applications [ 13 , 14 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this Special Issue “2D Nanostructures for Optoelectronic and Green Energy Devices”, we have collected nine high-quality, original research papers and one comprehensive review paper by outstanding scientists and engineers from relevant fields, covering the topics in optical properties and couplings in 2D nanostructures, [ 5 , 6 , 7 , 8 ] spectroscopic analysis in atomic scale, [ 9 ] 2D transistors, [ 10 , 11 ] 2D optoelectronics, [ 12 ] and 2D energy storage applications [ 13 , 14 ].…”
mentioning
confidence: 99%
“…Shin et al [ 6 ] reported interlayer coupling effects in 2D heterostructures using low-frequency Raman spectroscopy, offering a route to observe the quality of the interface in 2D nanostructures. Singh et al [ 7 ] and Pandey et al [ 8 ] reported optical coupling in nanostructures and substrates, which can be used in nanophotonics and detection applications. Yoon et al [ 9 ] reported the atomic arrangement of graphene-like ZnO examined using transmission electron spectroscopy.…”
mentioning
confidence: 99%